Innovative Strategies for Achieving Sustainable Development Goals Amidst Escalating Global Environmental and Social Challenges - Ruhana, Faria; Suwartiningsih, Sri; Mulyandari, Erni; Handoyo, Suryo; Afrilia, Ufa Anita (GoAcademica Research & Publishing, 2024)
In the face of escalating global environmental and social challenges, achieving the Sustainable Development Goals (SDGs) necessitates innovative strategies. This article conducts a comprehensive literature review to explore and synthesize diverse approaches towards sustainable development in an increasingly complex global landscape. By examining a broad range of scholarly publications, the study identifies key trends, challenges, and innovative solutions that have emerged in the pursuit of the SDGs. The analysis focuses on the integration of technological advancements, policy innovations, and community-driven approaches in addressing environmental degradation, social inequality, and economic challenges. The findings reveal that while progress has been made, significant gaps remain in effectively implementing and scaling sustainable solutions. The study highlights the critical role of interdisciplinary collaboration, policy integration, and inclusive governance in overcoming these challenges. It also emphasizes the need for aligning economic growth with environmental and social sustainability. The article concludes by proposing a framework for effective SDG implementation, calling for a holistic approach that integrates environmental conservation, social equity, and economic viability. This study contributes to the ongoing discourse on sustainable development, offering insights for policymakers, practitioners, and researchers in developing comprehensive strategies for achieving the SDGs.